Network Disruption and the Common-Enemy Effect - Hoyer, Britta; De Jaegher, Kris (International Journal of Game Theory)

Differences in NPI strategies against COVID-19 - Redlin, Margarete (Journal of Regulatory Economics)
Abstract Non-pharmaceutical interventions are an effective strategy to prevent and control COVID-19 transmission in the community. However, the timing and stringency to which these measures have been implemented varied between countries and regions. The differences in stringency can only to a limited extent be explained by the number of infections and the prevailing vaccination strategies. Our study aims to shed more light on the lockdown strategies and to identify the determinants underlying the differences between countries on regional, economic, institutional, and political level. Based on daily panel data for 173 countries and the period from January 2020 to October 2021 we find significant regional differences in lockdown strategies. Further, more prosperous countries implemented milder restrictions but responded more quickly, while poorer countries introduced more stringent measures but had a longer response time. Finally, democratic regimes and stronger manifested institutions alleviated and slowed down the introduction of lockdown measures.
Keywords: Economics and Econometrics

Modelling artificial intelligence in economics - Gries, Thomas; Naudé, Wim (Journal for Labour Market Research)
Abstract We provide a partial equilibrium model wherein AI provides abilities combined with human skills to provide an aggregate intermediate service good. We use the model to find that the extent of automation through AI will be greater if (a) the economy is relatively abundant in sophisticated programs and machine abilities compared to human skills; (b) the economy hosts a relatively large number of AI-providing firms and experts; and (c) the task-specific productivity of AI services is relatively high compared to the task-specific productivity of general labor and labor skills. We also illustrate that the contribution of AI to aggregate productive labor service depends not only on the amount of AI services available but on the endogenous number of automated tasks, the relative productivity of standard and IT-related labor, and the substitutability of tasks. These determinants also affect the income distribution between the two kinds of labor. We derive several empirical implications and identify possible future extensions.
Keywords: General Medicine

The Market for Belief Systems: A Formal Model of Ideological Choice - Gries, Thomas; Müller, Veronika; Jost, John T. (Psychological Inquiry)
Keywords: General Psychology

Essays on Industrial Organization and Networks: Retail Bundling, Exclusive Dealing, and Network Disruption - Endres-Fröhlich, Angelika Elfriede

Does education have an impact on patience and risk willingness? - Tawiah, Beatrice Baaba (Applied Economics)

Die Luftfahrt zwischen Liberalisierung und Konsolidierung - eine wettbewerbspolitische Analyse von Low-Cost- und Networkairlines - Bas, Sahin

Unternehmenszusammenschlüsse von Supermärkten - eine wettbewerbspolitische Analyse am Beispiel von Edeka und Kaiser's Tengelmann - Erdogan, Yeliz

Zum Potenzial von Kryptowährungen. Eine ökonomische Analyse zu den Chancen und Risiken digitaler Währungen - Perampalam, Abirame

Mergers on digital markets - An economic analysis - Nassar, Hamza